Current state of trauma and violence in São Paulo - Brazil during the COVID-19 pandemic - RIBEIRO-JUNIOR,MARCELO AUGUSTO FONTENELLE (2021)
ABSTRACT The coronavirus pandemic led society to adopt measures to contain its spread that generate impacts in the social, economic and psychological spheres, mainly due to social isolation. Some authors point out that social changes have generated changes in the various forms of trauma and violence. For this study, data collection for the years 2019 and 2020 was carried out on DATASUS - TABNET and on the website of the Secretariat of Public Security - SSP, considering various types of trauma and violence, with subsequent correlation analysis using the Kendall coefficient and correlation test. There was statistical significance, allowing a correlation with the negative pandemic for the rates of body injury due to traffic accidents, gunshot injuries, stab wounds, sexual violence, bodily injuries and interpersonal violence. As factors possibly associated with a reduction in the incidence of these variables, the literature presents some changes resulting from the pandemic, such as adherence to isolation, with a reduction in the flow of people on the street, and a decrease in reports of violence. The present study indicates that the findings may serve as a warning for future changes and for the adoption of preventive measures, however they represent the initial situation of the pandemic in São Paulo and, therefore, further investigations must be carried out with the course of the pandemic, which still remains.